2017
DOI: 10.1186/s13012-017-0601-0
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of a de-implementation strategy to reduce low-value blood management techniques in primary hip and knee arthroplasty: a pragmatic cluster-randomized controlled trial

Abstract: BackgroundPerioperative autologous blood salvage and preoperative erythropoietin are not (cost) effective to reduce allogeneic transfusion in primary hip and knee arthroplasty, but are still used. This study aimed to evaluate the effectiveness of a theoretically informed multifaceted strategy to de-implement these low-value blood management techniques.MethodsTwenty-one Dutch hospitals participated in this pragmatic cluster-randomized trial. At baseline, data were gathered for 924 patients from 10 intervention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 54 publications
0
33
0
1
Order By: Relevance
“…The steps include creating conditions for change, engaging in sense‐making conversations with care teams and allowing them to take a sense of ownership of the issue to make their own decision about where the balance of benefit and harm lies. Finally, several studies have adapted the Theoretical Domains Framework to guide or interpret de‐implementation findings . The Theoretical Domains Framework synthesizes psychological theories of behaviour change to help develop theoretically grounded behaviour‐change interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The steps include creating conditions for change, engaging in sense‐making conversations with care teams and allowing them to take a sense of ownership of the issue to make their own decision about where the balance of benefit and harm lies. Finally, several studies have adapted the Theoretical Domains Framework to guide or interpret de‐implementation findings . The Theoretical Domains Framework synthesizes psychological theories of behaviour change to help develop theoretically grounded behaviour‐change interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Individual factors are linked to contextual factors and must be considered before de‐implementation is initiated. All stakeholders should recognize that it is more difficult to terminate clinical practices entirely than to substitute a new or modified clinical practice . Using Roger's terminology (2003), it may be helpful to determine if an individual is considered a laggard or late adopter or an early adopter.…”
Section: Resultsmentioning
confidence: 99%
“…Of 19 articles, 17 lacked a control group (Yazer & Waters, ; King et al, ; Freedman, ; Goodnough & Shah, ; Smith et al, ; Tavares et al, ; Watson & Kendrick, ; Yerrabothala et al, ; Boral et al, ; Butler et al, ; Goodnough & Shah, ; Hibbs et al, ; Murphy & Goodnough, ; Borgert et al, ; Patel et al, ; Hicks et al, ; Norgaard et al, ). Efforts to conduct controlled trials are sparse ( Hartley et al, ; Voorn et al, ). In addition, in nine studies, the implementation strategies were chosen based on literature (Yazer & Waters, ; Freedman, ; Goodnough & Shah, ; Smith et al, ; Yerrabothala et al, ; Butler et al, ; Goodnough & Shah, ; Borgert et al, ; Norgaard et al, ).…”
Section: Patient Blood Managementmentioning
confidence: 99%
“…In the LISBOA study, the strategy was tested in a cluster‐randomised controlled trial, with clusters formed by individual hospitals. The results demonstrated that in both the intervention group exposed to the de‐implementation strategy and the control group, the use of ESAs and blood salvage reduced (Voorn et al, ). In other words, the de‐implementation strategy was not effective.…”
Section: The Lisboa Studymentioning
confidence: 99%
See 1 more Smart Citation